DETECTION OF NEUROSENSORY RETINAL DETACHMENT COMPLICATING DEGENERATIVE RETINOSCHISIS BY ULTRA-WIDEFIELD FUNDUS AUTOFLUORESCENCE IMAGING. Issue 5 (May 2020) - Francone, Anibal; Kothari, Nikisha; Farajzadeh, Matthew; Hosseini, Hamid; Prasad, Pradeep; Schwartz, Steven; Hubschman, Jean Pierre
Abstract : Purpose: To determine whether neurosensory retinal detachment complicating degenerative retinoschisis (RS) can be reliably detected with ultra-widefield fundus autofluorescence evaluation. Methods: Consecutive patients diagnosed with RS who had ultra-widefield fundus autofluorescence imaging were included in this retrospective case series. According to the fundus autofluorescence patterns, we divided the eyes into two groups: 1) eyes with RS and a hyperautofluorescent leading edge and 2) eyes with RS and without hyperautofluorescence. Peripheral spectral domain optical coherence tomography images at the level of RS were obtained. Results: Thirty-eight eyes that met eligibility criteria were identified. Review of ultra-widefield fundus autofluorescence demonstrated 21/39 (55%) eyes with distinctive hyperautofluorescence over the area of RS (Group A) and 17/38 (45%) eyes without any form of hyperautofluorescence (Group B). Spectral domain optical coherence tomography images confirmed the presence of full-thickness neurosensory retina separation from the underlying retinal pigment epithelium in the areas of hyperautofluorescence in 10/10 eyes (100%) from Group A. None (0/11; 0%) of the eyes from Group B showed full-thickness neurosensory retina separation on the spectral domain optical coherence tomography imaging of the retina–RS interface. Conclusion: Hyperautofluorescent findings suggest the presence of a neurosensory retinal detachment. Retinal detachment associated with RS can be reliably detected on ultra-widefield fundus autofluorescence and may be a useful diagnostic imaging modality. Abstract : Ultra-widefield fundus autofluorescence imaging reveals abnormalities in degenerative retinoschisis that allow for the identification of an associated neurosensory detachment confirmed by spectral domain optical coherence tomography.